A pedagogia da alternância na casa familiar rural de Senador José Porfírio, Pará: aplicação na prática com educandos das comunidades de Porto de Moz - MATOS, José Benedito Sanches de (2021)
The Alternation Pedagogy consists of a methodology of organization of school education that combines different training experiences distributed over different times and spaces, aiming at professional training. This work aims to analyze the implementation of the Pedagogy of Alternation of the Rural Family House of Senador José Porfírio in relation to the Professional Project of Young People (PPJ) of graduates of riverside communities of Porto de Moz. The methodology used in this work was qualitative in order to understand how the theory and practice of the pedagogy of alternation in the CFR of Senador José Porfírio is being applied. Six people, two teachers and four students from different areas of the municipality of Porto de Moz were interviewed, being a student of the várzea area, two of the land area and one of the transition area. The entrance of the students of the municipality of Porto de Moz in the Rural Family House of Senador José Porfírio happened through a partnership between the two CFR's. This partnership took place not only to receive students, but also to articulate with municipal governments. The CFR of Senador José Porfírio was not prepared to receive such diverse cultures because it did not elaborate a curricular proposal to guarantee the treatment of the socio-environmental and productive specificities of the communities of Porto de Moz. The students had difficulty in designing and implementing the Young Professionals Project. No interviewee was able to finalize his project in practice. The CFR with the Alternation Pedagogy method needs to actually put the instruments or tools into practice, by which discussions can be made on integrating diversity of identities, and without these tools the CFR does not offer differentiated education.